Sectors and Businesses Facing COVID-19: Emergency and Reactivation - Economic Commission for Latin America; the Caribbean (United Nations, 2020)
This Special Report is the fourth in this series on the evolution and impacts of the COVID-19 pandemic in Latin America and the Caribbean. The economic crisis generated by coronavirus disease (COVID-19) is having a major impact on the countries of Latin America and the Caribbean and is hitting a productive and business structure with weaknesses that have been building up for decades. Before the pandemic, the region’s production structure already showed great structural heterogeneity that seriously limited its economic development possibilities. The pandemic makes these weaknesses more evident and amplifies economic, social and environmental tensions. In the arena of production, it is urgent to mitigate capacity destruction, without neglecting the need for a sustained increase in productivity, the generation of productive linkages and increased learning and the generation and dissemination of innovations. In this context, manufacturing is of strategic importance and must play a leading role in the growth process and in changing the productive matrix. This requires policies to change the production structure. In other words, incentives other than those that currently prevail for private companies, together with the State, to make the necessary investments to diversify the economic structure, ensure a continuous and stable growth process and avoid social and environmental setbacks.